Mental Accounting and Heuristics for Personal Finance Management Among University Students: Exploring the Emerging Role of Islamic Perspectives - Sinaga, Tiur Enjel; Grania Mustika, Ira; Desyana, Gita (IJIBE (International Journal of Islamic Business Ethics), 2024)
Parents have increasingly limited control over their children's spending and consumption choices. Therefore, each individual needs to hone good money management skills in order to make wise financial decisions. Often they spend carelessly and irrationally when they do not have good money management, resulting in poor money management. The purpose of this study was to determine how heuristics and mental accounting can be used in personal financial management. This study was conducted primarily on students who have not worked at the Faculty of Economics and Business, Tanjungpura University, Pontianak. A systematic literature review approach was used in this investigation. The findings show that most of the study respondents are still in the process of learning to use mental accounting, and the use of heuristics by students from the Faculty of Economics and Business (FEB) at Tanjungpura University in Pontianak is still lacking. Three main factors contribute to mental accounting and poor implementation of heuristics: low motivation, limited experience, and lack of information. Even though the sorting of the post has been completed, for students who have used mental accounting. However, this is impossible to achieve in practice because the respondents' financial decision making (heuristics) usually uses them to consume rather than save or invest.